Mitochondria As Sources and Targets of Methane - Mészáros, András Tamás; Szilágyi, Ágnes Lilla; Juhász, László; Tuboly, Eszter; Érces, Dániel; Varga, Gabriella; Hartmann, Petra (Frontiers in Medicine, 2017)
This review summarizes the current knowledge on the role of mitochondria in the context of hypoxic cell biology, while providing evidence of how these mechanisms are modulated bymethane (CH4). Recent studies have unambiguously confirmed CH4 bioactivity in various in vitro and in vivo experimental models and established the possibility that CH4 can affect many aspects of mitochondrial physiology. To date no specific binding of CH4 to any enzymes or receptors have been reported and it is probable that many of its effects are related to physico-chemical properties of the non-polar molecule. (i) Mitochondria themselves can be sources of endogenous CH4 generation under oxido-reductive stress conditions; chemical inhibition of the mitochondrial electron transport chain with site specific inhibitors leads to increased formation of CH4 in eukaryote cells, in plants and animals. (ii) Conventionally believed as physiologically inert, studies cited in this review demonstrate that exogenous CH4 modulates key events of inflammation. The anti-apoptotic effects of exogenously-administered CH4 are also recognized, and these properties also suggest that CH4-mediated intracellular signalling is closely associated with mitochondria. (iii) Mitochondrial substrate oxidation is coupled to reduction of molecular oxygen, thus providing energy for cellular metabolism. Interestingly, recent in vivo studies have shown improved basal respiration and modulated mitochondrial oxidative phosphorylation by exogenous CH4. Overall, these data suggest that CH4 liberation and effectiveness in eukaryotes are both linked to hypoxic events and redox regulation, and support the notion that CH4 has therapeutic roles in mammalian pathophysiologies.